A Genome-Wide Association Study Primer for Clinicians - Tzu-Hao Wang; Hsin-Shih Wang (Elsevier, 2009)
Genome-wide association studies (GWAS) use high-throughput genotyping technology to relate hundreds of thousands of genetic markers (genotypes) to clinical conditions and measurable traits (phenotypes). This review is intended to serve as an introduction to GWAS for clinicians, to allow them to better appreciate the value and limitations of GWAS for genotype-disease association studies. The input of clinicians is vital for GWAS, since disease heterogeneity is frequently a confounding factor that can only really be solved by clinicians. For diseases that are difficult to diagnose, clinicians should ensure that the cases do indeed have the disease; for common diseases, clinicians should ensure that the controls are truly disease-free.